GE_GERICHTE P/26137/2017 vom 27. November 2019 - GE Cour de justice (2019)
DÉFAUT(CONTUMACE);INCAPACITÉ DE TRAVAIL;EMPÊCHEMENT NON FAUTIF;DÉPLACEMENT(SENS GÉNÉRAL);CERTIFICAT MÉDICAL | CPP.205; CPP.355